Pertanggungjawaban negara dalam kejahatan genosida menurut hukum internasional - Vivi Amelia Amelia (Jurnal Kedaulatan Hukum, 2025)
Genocide is defined by the 1948 Genocide Convention as an attempt to destroy, in whole or in part, a group based on its national, ethnic, racial, or religious identity. The United Nations has a crucial duty and authority to address the crime of genocide. Therefore, the United Nations must conduct its operations in accordance with its charter. Conversely, preventing and addressing genocide using international legal instruments such as the Genocide Convention and the Rome Statute still faces significant challenges, such as political challenges and poor preventive measures. Genocide, defined as the systematic destruction of a particular ethnic, racial, or religious group, challenges law enforcement worldwide. According to Article 77 of the Rome Statute, those who commit genocide can be subject to imprisonment, fines, or confiscation. The enforcement of international law is considered fair because the International Court of Justice does not discriminate on the basis of the nation, ethnicity, or status of the perpetrators. It is hoped that this research will broaden our knowledge of the crime of genocide and provide policy recommendations to strengthen the enforcement of international justice and enhance protection for vulnerable groups.